-3(x-1)=-2x-3

Simple and best practice solution for -3(x-1)=-2x-3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3(x-1)=-2x-3 equation:


Simplifying
-3(x + -1) = -2x + -3

Reorder the terms:
-3(-1 + x) = -2x + -3
(-1 * -3 + x * -3) = -2x + -3
(3 + -3x) = -2x + -3

Reorder the terms:
3 + -3x = -3 + -2x

Solving
3 + -3x = -3 + -2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '2x' to each side of the equation.
3 + -3x + 2x = -3 + -2x + 2x

Combine like terms: -3x + 2x = -1x
3 + -1x = -3 + -2x + 2x

Combine like terms: -2x + 2x = 0
3 + -1x = -3 + 0
3 + -1x = -3

Add '-3' to each side of the equation.
3 + -3 + -1x = -3 + -3

Combine like terms: 3 + -3 = 0
0 + -1x = -3 + -3
-1x = -3 + -3

Combine like terms: -3 + -3 = -6
-1x = -6

Divide each side by '-1'.
x = 6

Simplifying
x = 6

See similar equations:

| 2a-21=a | | 12x-11y=23 | | 3/13=u/10 | | 5(2x+5)-1=-2x | | 2b-48+2b-96=180 | | 3u-64=u | | 10y+9=13y+3 | | 3n+4(5n+2)=8+3n | | 16z-21+2z+39=180 | | -3(1-5m)+4=1-2m | | 7=an-1+-15 | | 4c-65=5c-85 | | 4c-65=5c-68 | | -2+3p=6p-4-2p | | 7y+73=4y+94 | | -5+6m=5m-8 | | t=2t-51 | | 3y=-x-2 | | 4y-5x=4y-5x | | 8/9-5/6×1/3 | | 4b+64=2b+68 | | 8n-n=-4+6n | | 7c-77=4c-35 | | -4x+4=11+2x-7x | | 9x+16y=7 | | 2/y-3=3/y | | 3q+6=6q | | 3+3(2-6)= | | -5+6x=x+10 | | 2s-48=s | | 2s+40=4s+28 | | x/3-=11 |

Equations solver categories